STEM CUTTING TECHNIQUE FOR OFF SEASON HYBRIDIZATION IN DIFFICULT CROSSES IN POTATO IN NW HILLS - Dhiman, K. R.; Manivel, P; Kumar, Vinod; Sharma, Sonu (Potato Journal, 2013)
The shoot cuttings of 26 genotypes treated with rootex were planted during August for generation of dihaploids during off season. The results indicated that the period of potato hybridization in case of medium and late maturing genotypes can be extended by shoot cutting technique. The early maturing genotypes, however didn’t respond. After pollination with dihaploid inducer parent, berries and seeds could be obtained. The berry setting percentage ranged from 0 to 36.67%.